The Psychosocial Impact on Nurses in The First Three Months of Covid-19 Outbreak - Hapsah Hapsah; A. AS; Rasmawati; Wahyuni Wahyuni (Indonesian Contemporary Nursing Journal, 2022)
Introduction: This study aimed at identifying psychosocial impact on nurses in the first three months of Covid-19  Outbreak  in  various  Indonesian  regions.  Method: There were  585 respondents as nurses met requirements from 920  (accidental sampling) filled out the online survey from 1500 attendees participated in  Mental Health Nursing Webinar conducted by the Indonesian National Nurses Association (PPNI) of South Sulawesi (27th June 2020). Self- Reporting Questionnaires (SRQ29 as psychosocial and additional symptoms  screening tool were distributed as online form with informed consent an hour before the online meeting started. Result: the age average of the respondents was 32 years old, more than a half of them were female (70.3%), and worked in hospital (61.9%). There were 7 symptoms identified in this study, where 40.2% of respondents experienced anxiety, depression symptoms (21%), somatic symptoms (37.8%), cognitive decline (21.2%), energy decreased (30.8%), post-traumatic stress (29.2%), psychotic symptoms (11.5%), and drug abuse (0.9%). Conclusion: The psychosocial impact of  Covid-19 outbreak in  the  first three  months was fairly high on nurse population.  Therefore, it is essential for further research to identify risk factors and how to handle them.